2016
DOI: 10.1631/jzus.b1500248
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide from a NaHS source attenuates dextran sulfate sodium (DSS)-induced inflammation via inhibiting nuclear factor-κB

Abstract: This study investigated the alleviating effects of hydrogen sulfide (H2S), derived from sodium hydrosulfide (NaHS), on inflammation induced by dextran sulfate sodium (DSS) in both in vivo and in vitro models. We found that NaHS injection markedly decreased rectal bleeding, diarrhea, and histological injury in DSS-challenged mice. NaHS (20 μmol/L) reversed DSS-induced inhibition in cell viability in Caco-2 cells and alleviated pro-inflammation cytokine expression in vivo and in vitro, indicating an anti-inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The reduction of inflammation was as effective as SASP, a commonly used medical therapy [ 53 ]. Chen et al also reported in dextran sulfate sodium (DSS)-induced colonic inflammation that NaHS treatment decreased inflammation and tissue injury in mice [ 54 ]. However, the protective mechanism of H 2 S is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of inflammation was as effective as SASP, a commonly used medical therapy [ 53 ]. Chen et al also reported in dextran sulfate sodium (DSS)-induced colonic inflammation that NaHS treatment decreased inflammation and tissue injury in mice [ 54 ]. However, the protective mechanism of H 2 S is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen sulfide therapy has attracted significant attention as a potent biological mediator. Although its benefits have been appreciated in different gastrointestinal disease models like colitis (Fiorucci et al., 2007; Chen and Liu, 2016) and intestinal ischemia/reperfusion injury (Henderson et al., 2010; Jensen et al., 2018), its potential effect on POI has not yet been investigated. POI is a serious complication seen after abdominal surgery, leading to impairment of the gastrointestinal transit that traditionally was thought to result from neuronal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up studies can be performed to unravel the underlying mechanisms by which these H 2 S-releasing compounds exert their beneficial effects in the murine model of POI. The most frequently described mechanisms by which exogenous H 2 S exerts its anti-inflammatory effect are inhibition of the pro-inflammatory nuclear transcription factor-κB (Oh et al., 2006; Li et al., 2013; Chen and Liu, 2016), activation of the anti-oxidant nuclear factor erythroid 2–related factor 2 (Shimada et al., 2015; Xie et al., 2016; Qiu et al., 2018) and inhibition of the mitogen-activated protein kinase signaling pathways like p38 and extracellular signal-regulated kinase 1/2 (Hu et al., 2007; Xu et al., 2013). Furthermore, it can be investigated whether the endogenous H 2 S pathway is upregulated during POI as a protective mechanism, whereby exogenous H 2 S donors then strengthen this reaction; enhanced H 2 S synthesis with increased expression of H 2 S synthetizing enzymes at sites of mucosal ulceration was indeed demonstrated in rat colitis (Wallace et al., 2009; Flannigan et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that NLRP3 inflammasome mediated dextran sodium sulfate (DSS)-induced colitis. H2S could reduce the inflammation of colitis induced by DSS through inhibiting the activation of NF-κB pathway, so it could be infered that H 2 S could relieve DDS-induced colitis through suppressing NLRP3 inflammasome via NF-κB pathway, which neede further study [92][93][94][95]. In DSS-induced colitis, H 2 S decreased the protein expression level of NLRP3 inflammasome, pro-caspase-1, and Nrf2 and the silencing Nrf2 has the effects similar to the above, which indicated that H 2 S inhibited NLRP3 inflammasome through Nrf2 pathway [96].…”
Section: H 2 S Plays a Protective Role In Other Inflammatory Reactions By Inhibiting Nlrp3 Inflammasomementioning
confidence: 99%